2010
DOI: 10.1007/s00535-010-0334-1
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor versus prokinetic therapy in patients with functional dyspepsia: is therapeutic response predicted by Rome III subgroups?

Abstract: The effectiveness of proton pump inhibitor therapy and that of prokinetic therapy in functional dyspepsia are not different, and cannot be predicted by Rome III subgroups (ClinicalTrials.gov number, NCT00663897).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Subgroup analysis suggests that those patients who have more prominent heartburn-related symptoms respond better to PPI therapy ( 119 ) but there is no evidence that epigastric pain syndrome responds better than postprandial distress syndrome type dyspepsia ( 115 ). We therefore do not recommend using the type of symptom in FD to guide treatment choice.…”
Section: Strong Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…Subgroup analysis suggests that those patients who have more prominent heartburn-related symptoms respond better to PPI therapy ( 119 ) but there is no evidence that epigastric pain syndrome responds better than postprandial distress syndrome type dyspepsia ( 115 ). We therefore do not recommend using the type of symptom in FD to guide treatment choice.…”
Section: Strong Recommendation Moderate Quality Evidencementioning
confidence: 99%
“…These results are compatible with a previous study. Hsu et al 8 reported similar symptom improvement (~50%) with 30-mg lansoprazole and mosapride in 329 patients with FD.…”
Section: Discussionmentioning
confidence: 84%
“…22 There are few studies directly comparing the efficacy of PPIs and prokinetics in Asia. Hsu et al 8 reported that the efficacy of PPI was similar to prokinetics in patients with FD according to the Rome III criteria after 2 weeks of treatment. In another study of 23 The co-administration of PPI and prokinetics is commonly prescribed for patients with FD and is frequently recommended by clinical guidelines, although the efficacy has been questioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton-pump inhibitors (PPI) and prokinetic agents are the mainstays of the treatment of FD [39], both of which have similar relative efficacy [42]. However, adverse events related to PPI have been reported, and the comparative efficacy of prokinetics has thus far not been evaluated [43, 44].…”
Section: Discussionmentioning
confidence: 99%